Touching the base: heart-warming ads from the 2016 U.S. election moved viewers to partisan tears - Seibt, B. (2018)
Some political ads used in the 2016 U.S. election evoked feelings colloquially known as being moved to tears. We conceptualise this phenomenon as a positive social emotion that appraises and motivates communal relations, is accompanied by physical sensations (including lachrymation, piloerection, chest warmth), and often labelled metaphorically. We surveyed U.S. voters in the fortnight before the 2016 U.S. election. Selected ads evoked the emotion completely and reliably, but in a partisan fashion: Clinton voters were moved to tears by three selected Clinton ads, and Trump voters were moved to tears by two Trump ads. Viewers were much less moved by ads of the candidate they did not support. Being moved to tears predicted intention to vote for the candidate depicted. We conclude that some contemporary political advertising is able to move its audience to tears, and thereby motivates support.